John and Elaine in Poland - unknown:::Creator::::::::::::
John and Elaine Steinbeck stand and look at a case in Wawel Castle (Zamek wawelski) in Poland. The castle was built in 1500s under auspices of Krol Zygmunt I. Original in safe